Emerging of Avian Leukosis Sub-group J (ALV - J) Infections in Broiler Chickens in Malaysia - Hair-Bejo, M.; Ooi, P.T.; Phang, W.S. (International Journal of Poultry Science, 2004)
Recent outbreaks of Newcastle disease (ND) in commercial chickens in Malaysia was associated with infiltration of myeloid cells in the organs of the affected chickens which has not been reported previously and was consistent to those of Avian Leukosis Sub-group J (ALV-J) infection. However, little is known about the disease and it was the objective of the study to determine the sero-prevalence and lesions of ALV-J infection in broiler chickens. Broiler breeders (120) of 66-week-old from two breeder farms in Selangor and Malacca were used in the study. They were divided into 4 groups namely groups A1 (30 hens) or A2 (30 cocks) and B1 (36 hens) or B2 (24 cocks) of chickens from Selangor and Malacca, respectively. The broiler chickens (125) of 5-week-old were sampled from four broiler farms in Johor identified as groups C, D, E and F. The clinical signs were recorded and serum samples were collected for ALV-J antibody detection using enzyme linked immunosorbent assays (ELISA) technique. On necropsy, the gross lesions were recorded. Samples of brain, liver, spleen, kidney, lung, ribs and sciatic nerve, and bursa of Fabricius were collected from the broiler breeders and broilers, respectively for histopathology. The study showed that 10% of the broiler breeder had mild lameness, mainly due to bumble foot (83%). Fatty livers (12%), Pasteurella multocida infections (4%) and splenomegaly (2.5%) were also recorded. The chickens in the group C and D had complicated chronic respiratory disease (CCRD). Histologically, infiltrations of myeloid cells were found in the liver of a bird from the group A1. Infiltration of myeloid cells in the follicles of the bursa of Fabricius was also observed in chickens from groups C (10%), D (20%), E (50%) and F (30%). Moderate to severe lesion scoring of the bursa of Fabricius was recorded. The ALV-J antibody was detected in breeder chickens in groups A1 (27%), A2 (27%), B1 (36%) and B2 (42%), but was not detected in the broiler chickens. It was concluded that broiler breeder chickens in Malaysia is not free from ALV-J infections. The overall sero-prevalence of ALV-J in the broiler breeder chickens was 33% with no differences between the hens and cocks. The presence of myeloid cells infiltration in the follicles of the bursa of Fabricius, 10 to 50% of the samples examined suggests that broiler chickens are at high risk of ALV-J infection.